Working through exceptional space: The case of women migrant workers in Mae Sot, Thailand. (May 2016) - Kusakabe, Kyoko; Pearson, Ruth
This article focuses on the borderland of Thailand with Myanmar and analyzes how Burmese women migrant workers are both victimized – Agamben's homo sacer – by the exceptional space of the borderland, but also are able to actively utilize the opportunities afforded by the particular space of the border to juggle their responsibilities and life options. The article focuses on how women migrant workers arrange their healthcare, childcare and children's education at the borderland of Mae Sot and in the centerland of Bangkok, and analyzes how they use the opportunities available at the border to manage these tasks. At the same time, the borderland leaves women with very weak protection against violence, cut off from their communities of origin, which offer both protection and control. Although borderlands can provide space for alternatives, this exceptional space compounded with a strict gender regime can pose serious restrictions on women's agency.